Investigation of Charge Transfer Complexes Formed between Mirtazapine and Some π-Acceptors - Hulya Demirhan; Mustafa Arslan; Mustafa Zengin; Mustafa Kucukislamoglu (Journal of Spectroscopy)
Charge transfer complexes (CTC) of mirtazapine with tetracyanoethylene (TCNE), 2,3-dichloro-5,6-dicyano-p-benzoquinone (DDQ), and tetracyanoquinodimethane (TCNQ) have been studied spectrophotometrically in dichloromethane at room temperature. The stoichiometries of the complexes were found to be 1 : 1 ratio by the Job Method between mirtazapine and the acceptors. The equilibrium constants and thermodynamic parameters of the complexes were determined by the Benesi-Hildebrand and Van't Hoff equations. Mirtazapine in pure and dosage form was applied in this study. The results indicate that the formation constants for the complexes depend on the nature of electron acceptors and donor. And also the spectral studies of the complexes were determined by FT-IR and NMR spectroscopy.